The Influence of Post in Endodontically Treated Molar Abutment on Fixed Dentures Success Rate - Pralita Kusumawardhini; Alysia Henrietta; Saraventi Saraventi (Faculty of Dentistry, Universitas Indonesia, 2013)
Many dentists believe that the tooth need reinforcement provided by post before the definite restoration is placed. However, others suggest not to use post when posterior teeth especially molars, still have significant amount of tooth structure. Therefore, when endodontically treated molar is considered to be used as fixed denture abut-ment, clinicians must have proper knowledge about the impact of post placement. This literature will describe considerations regarding post placement in endodontically treated molar abutment in fixed partial dentures and their influence to the success rate. Previous studies implied the need of proper measurement of the amount of remaining tooth structure, the type of intracoronal reinforcement of the abutment, and the functional loads to ensure the success of fixed denture treatment. When planning definitive restorations for endodontically treated abutment teeth, some even suggest to use post and core to fulfill the need of reinforcement. On the contrary, others find that when a post is use in endodontically treated abutment teeth, the failure of custom made-tapered cast post and core is relatively high, whereas the use of amalgam or composite core in posterior teeth especially molars with adequate amount of tooth structure is sufficient due to post system's limited influence on the suc-cess rate. Based on literature review, for cases with adequate tooth stucture, it can be concluded that the influ-ence of post placement in endodontically treated molar abutment to fixed partial dentures success rate is very limited. DOI: 10.14693/jdi.v18i2.64